The Importance of seismic microzonation under the threat of an earthquake of the north anatolian fault in nilufer, bursa, turkiye - Bicakci, Guldane Boyraz; Ozcep, Ferhat; Karabulut, Savaş; Cengiz, Mualla (Elsevier, 2024)
The Nilufer district experienced the most recent urbanization among the central districts of Bursa in South Marmara region with the completion of rapid construction. Since 358 BCE, many destructive earthquakes were reported on the branches of the North Anatolian Fault (NAF) which caused extensive damage to buildings and loss of life near Bursa city. Besides some studies conducted to define the soil behavior in the vicinity of Bursa, a seismic hazard study in Nilufer is still lacking. We, therefore, carried out a microzonation study including the following steps. First, an earthquake hazard analysis was conducted and the peak ground acceleration (PGA) values were determined for an expected earthquake. In the next step, MASW (Multi-Channel Analysis of Surface Wave) measurements conducted at 54 points in 28 neighbourhoods of Nilufer district were evaluated. Soil mechanical parameters were determined at 11 boreholes to assess the liquefaction potential. It was found that almost half of the study area suffers from low damage considering only the vulnerability index (Kg) index, which depends on the site effect. Therefore, in addition to the Kg values, we created a microzonation map using the results of soil liquefaction, settlement, changes in groundwater level, and the average values of spectral acceleration. The study area is classified by four damage levels changing from low to high. Using only the Kg index could not quantify the potential damage level in the study area, thus we showed that the districts of Altinsehir, Hippodrome, Urunlu and Alaaddinbey, Ertugrul, 29 Ekim, 23 Nisan, Ahmetyesevi and Minarelicavus were identified at potentially high-risk damage zones. The results of this study clearly showed that considering the Kg index, which depends only on the local site effect, may lead to inadequate damage values.
Keywords: Bursa; Nilufer; MASW; Site effect; Liquefaction; PGA; Vulnerability Index; Microzonation